Prioritas Masalah dan Solusi dalam Proses Pembelajaran Mahasiswa Program Studi Akuntansi - Yohana Ayu Rahardjo (Jurnal Bingkai Ekonomi (JBE), 2020)
This study aims to determine the priority of problems and solutions in the learning process in the SWCU FEB accounting study program. The data used in this study is primary data using respondents accounting class 2015, 2016, and 2017. The methods used in determining the priority of problems and priority solutions in this study using the Analytic Hierarchy Process (AHP) method. The results of the analysis show the priority of problems in the learning process is from the aspect of hard skills. Furthermore, the solution to the priority of hard skill problems is from the aspect of curriculum design. With a well-developed and appropriate curriculum design can be an effort to improve student hard skills.